PELATIHAN REGULASI EMOSI UNTUK MEMBENTUK EMOSI POSITIF REMAJA DI PASIR TANJUNG, TANJUNGSARI, BOGOR - Zarina Akbar; Mauna; Ernita Zakiah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
Abstract Adolescence is a phase full of turmoil that often causes psychological problems such as stress. Some stressors, such as conflict and tension, affect adolescents' negative emotions. This makes them tend to follow their emotions in their behaviors and actions. Adolescents filled with negative emotions can have a negative influence on others, have concentration problems, always or like to be alone, have self-adjustment struggles, and be not focused. Emotion problems in adolescents include anxiety or depression, social withdrawal or stress, social issues, thinking problems, concentration problems, behavior that violates rules or norms, and lastly aggressive behavior. The ups and downs of emotions experienced by adolescents make the ability to control emotions crucial. One of the psychological aspects that can reduce negative emotions and increase positive emotions is emotional control. The ability of individuals to manage and control emotions is called emotional regulation. Emotional regulation is the ability of individuals to manage and control their thoughts, behaviors, and expressions related to the emotions they are feeling. The participants of this community service were teenagers in Pasir Tanjung Village, Tanjungsari Sub-district, Bogor. The program was carried out by providing training on emotional regulation. Keywords: training; adolescence; emotional regulation; positive emotion Abstrak Remaja adalah fase yang penuh dengan gejolak yang sering menimbulkan masalah psikologis seperti stres. Ada beberapa stresor seperti konflik dan tekanan memungkinkan untuk memunculkan emosi negatif pada remaja. Hal ini membuat remaja cenderung mengikuti emosinya dalam perlakuan dan tindakan. Remaja yang dipenuhi emosi negatif mampu memengaruhi orang lain dengan negatif, sulit berkonsentrasi, selalu atau senang menyendiri dan juga tidak fokus dan mengalami kesulitan dalam penyesuaian diri. Permasalahan emosi pada remaja antara lain kecemasan atau depresi, menarik diri atau tertekan, keluhan somatik, masalah sosial atau pergaulan, kesulitan berpikir, kesulitan konsentrasi, perilaku melanggar aturan atau norma, dan yang terakhir perilaku agresif. Kondisi naik turunnya emosi yang dialami remaja membuat kemampuan mengontrol emosi menjadi sengat penting. Salah satu aspek psikologis yang mampu menurunkan emosi negatif dan meningkatkan emosi positif adalah dengan cara mengendalikan emosi, kemampuan individu dalam mengendalikan dan mengontrol emosi disebut regulasi emosi. Regulasi emosi merupakan kemampuan individu untuk mengelola dan mengontrol pikiran, perilaku, serta ekspresi terkait emosi yang sedang dirasakannya. Subjek pengabdian masyarakat adalah remaja di Pasir Tanjung, Tanjungsari, Bogor. Kegiatan dilaksanakan dengan memberikan pelatihan tentang regulasi emosi. Keywords: pelatihan; remaja; regulasi emosi; emosi positif